Akibat Hukum Profesi Jabatan Notaris Terkait Keterlibatan Notaris dalam Struktur Perseroan Terbatas oleh Majelis Pengawas - Darmansyah, Adimas Gusti; Rasji, Rasji (Universitas Ekasakti, 2023)
The case involves a lawsuit by Tamrin Irawan, Commissioner of PT Triocom, against PT Triocom, Notary Soehendro Gautama, Yuwanky, and Notary Yondri Darto. The lawsuit focuses on allegations of Unlawful Acts by Defendants II and III, suspected of conspiring in the elimination of shares and the dismissal of Tamrin Irawan as Commissioner without a valid GMS. The lawsuit centers on the falsehood of the Deed of Amendment of PT Triocom and the establishment of PT Triocom Citra Mandiri. The claim for damages includes material and immaterial losses of IDR 35 billion and IDR 39.5 billion. However, legal issues arise regarding the prohibition for a Notary to concurrently hold a position as a leader or employee of a private business entity, which can affect their position when the company goes bankrupt. UUJN does not explicitly address situations where a Notary is declared bankrupt in their personal capacity or as a leader of a company. Actions by a Notary holding a position in a limited liability company may result in legal consequences, such as the imposition of administrative sanctions, including oral reprimands, written reprimands, temporary suspension, honorable dismissal, or dismissal without honor for the reported Notary. In response to allegations of violations of ethical codes and the Notary's position, the Notary Supervisory Board will conduct a gradual examination if there are reports from the public, starting from the Regional Supervisory Board in the District/City to the Central Supervisory Board in the Capital City. The authorities of each institution are different